Three Dimensional Honeycomb Patterned Fibrinogen Based Nanofibers Induce Substantial Osteogenic Response of Mesenchymal Stem Cells. Issue 1 (December 2017) - Nedjari, Salima; Awaja, Firas; Altankov, George
Abstract Stem cells therapy offers a viable alternative for treatment of bone disorders to the conventional bone grafting. However clinical therapies are still hindered by the insufficient knowledge on the conditions that maximize stem cells differentiation. Hereby, we introduce a novel 3D honeycomb architecture scaffold that strongly support osteogenic differentiation of human adipose derived mesenchymal stem cells (ADMSCs). The scaffold is based on electrospun hybrid nanofibers consisting of poly (L-lactide ε-caprolactone) and fibrinogen (PLCL/FBG). Classical fibers orientations, random or aligned were also produced and studied for comparison. The overall morphology of ADMSC's generally followed the nanofibers orientation and dimensionality developing regular focal adhesions and direction-dependent actin cytoskeleton bundles. However, there was an initial tendency for cells rounding on honeycomb scaffolds before ADMSCs formed a distinct bridging network. This specific cells organization appeared to have significant impact on the differentiation potential of ADMSCs towards osteogenic lineage, as indicated by the alkaline phosphatase production, calcium deposition and specific genes expression. Collectively, it was observed synergistic effect of nanofibers with honeycomb architecture on the behavior of ADMSCs entering osteogenic path of differentiation which outlines the potential benefits from insertion of such bioinspired geometrical cues within scaffolds for bone tissue engineering.